Urgensi Pendidikan Islam dalam Menjaga Kesehatan Mental Remaja di Lingkungan Sekolah pada Era Media Sosial - Yusuf, Muhammad; Rahmadani, Ayu Lika; Lestari, Yuni; Kurniawan, Dwi Setia (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2022)
The purpose of this study is to elaborate on how Islamic education contributes to maintaining the mental health of adolescent students in the midst of the increasingly massive development and influence of social media in today's era. The method used in this research is the library method, namely the search for data and information in the form of written sources related to the Minimum Competency Assessment. The data collection technique in this research is documentation, while the data analysis technique used is descriptive analysis. The contribution of Islamic education in maintaining the mental health of students can be done by instilling faith values ​​in students so that they are aware of their nature as God's creation, instilling awareness to always carry out worship, instilling an attitude of gratitude to students, and instilling a positive learning attitude.